Nomenclature of amyloid and amyloidosis. WHO-IUIS Nomenclature Sub-Committee. (World Health Organization, 1993)
This classification of amyloid and amyloidosis is based on the amyloid fibril proteins, followed by a designation of the fibril protein precursor. Additional information includes the protein type or variant (where applicable) and the clinical diagnosis.